Carbon‐Based Dual‐Ion Battery with Enhanced Capacity and Cycling Stability. Issue 23 (21st September 2018) - Yang, He; Shi, Xiaoyuan; Deng, Ting; Qin, Tingting; Sui, Lu; Feng, Ming; Chen, Hong; Zhang, Wei; Zheng, Weitao
Abstract: A high cycling stability of dual‐ion batteries is greatly challenging, as the size required for inserting anions matches only insufficiently with the interlayer spacing of graphite which is often used as positive electrode. Herein, an activated expanded graphite (AEG) electrode is successfully prepared via KOH treatment. The loose structure of AEG accommodates the volume expansion caused by anion intercalation, and the large specific surface area facilitates the immersion of electrolyte ions to afford more energy density. Thus, the cycling stability is largely enhanced without losing capacity. Matching with activated carbon as negative electrode and an ionic liquid electrolyte, the assembled dual‐ion battery achieves an energy density of 43 Wh kg −1 at the power density of 756 W kg −1 within a working window of 0–3.6 V. Specifically, the energy density retains 83 % after 50 cycles. Such effective and low‐cost electrode optimization opens up a new route toward full enhancement on the cycling performance of positive electrodes for dual‐ion batteries. Abstract : Better dual‐ion battery : Activated expanded graphite via a simple KOH treatment as positive electrode, matching with activated carbon negative electrode, enables optimum energy density and power density for a carbon‐based dual‐ion battery. Such excellence is merited by the loose structure and large specific surface area of activated expanded graphite.